pH responsive polymers in drug delivery - Mutalabisin, Muhammad Fathiy; Chatterjee, Bappaditya; Md. Jaffri, Juliana (A and V Publication, 2018)
Stimuli-responsive polymer or ‘intelligent’ polymer recently emerged as new potential for drug delivery. Some stimuli have been listed such as thermo, light, ultrasound and pH. In this review, one of the stimuli-responsive polymer which is pH responsive been described in brief including the gelling mechanism, common type of polymers, common applications and current challenges. pH responsive polymers have wide applications in drug delivery. The application mainly covers the site specific drug release in different physiological site. However tumor targeting or in situ gellying nature of these polymers are still in ‘proof-of concept’ stage. Therefore there is still need of crucial evaluation of such polymers and their applications. This review would highlight some important aspects of stimuli sensitive polymers focusing pH-sensitivity and recent reported applications.